2020
DOI: 10.1186/s12885-020-06759-8
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in lung cancer patients and its association with medical service cost and treatment choice in China

Abstract: Background: It is evident that comorbidity exacerbate the complexity of the management of lung cancer, however, limited research has been conducted to investigate the impact of comorbidity on health service utilization and cost, as well as the treatment choice among lung cancer patients. We examined the association of comorbidity with medical service utilization, cost and treatment choice among lung cancer patients in China. Methods: We used claims data from China Urban Employees' Basic Medical Insurance (UEBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
0
26
0
2
Order By: Relevance
“…Furthermore, a German study reflects that every additional comorbidity to an index disease is associated with an increase by the factor of 2.3 in medical contacts. Consequently, the number of comorbidities is associated with a significant increase in physician contacts compared to patients without comorbidity 17 . Considering that in 2007 the number of physician contacts for all statutory insured people in Germany was 17 18 , the disease burden of patients with lung cancer is underlined by the fact that they visited an outpatient care provider 35 times and have a CCI about 6.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a German study reflects that every additional comorbidity to an index disease is associated with an increase by the factor of 2.3 in medical contacts. Consequently, the number of comorbidities is associated with a significant increase in physician contacts compared to patients without comorbidity 17 . Considering that in 2007 the number of physician contacts for all statutory insured people in Germany was 17 18 , the disease burden of patients with lung cancer is underlined by the fact that they visited an outpatient care provider 35 times and have a CCI about 6.…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with lung cancer usually experience significant medical service utilization [ 37 ]. In clinical practice, IIV of Endostar has increased intravenous admixture workload of nursing staff, as Endostar should be diluted in 500 mL of normal saline daily for a duration of 14 days in each treatment cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the major contributors to cancer-caused DALYs in most countries, and has imposed a substantial disease burden to global public health [ 42 , 43 ]. China has experienced a noteworthy increase in the relative disease burden caused by lung cancer, with 12% of total DALYs from cancers in 1990 to 20% in 2008 [ 43 ], and is now facing up with severe predicament of lung cancer burden [ 37 ]. Currently, Endostar has been widely used in combination with first-line chemotherapy for advanced NSCLC in China.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of comorbidity is complex, long‐lasting, and uncertain due to the lack of appropriate coping strategies and the estimation of prognosis. Ding et al (2020) surveyed 8655 patients with lung cancer and found that 31.3% of them had at least one comorbid condition. Comorbidities aggravate the complexity of lung cancer management, and multiple comorbidities limit potential treatment options, thereby adding a significant medical burden.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of comorbidity is complex, long-lasting, and uncertain due to the lack of appropriate coping strategies and the estimation of prognosis. Ding et al (2020) surveyed 8655 patients with lung cancer and found that 31.3% of them had at least one comorbid condition.…”
Section: Introductionmentioning
confidence: 99%